2022
DOI: 10.3390/antiox11122315
|View full text |Cite
|
Sign up to set email alerts
|

Blocking TRPV4 Ameliorates Osteoarthritis by Inhibiting M1 Macrophage Polarization via the ROS/NLRP3 Signaling Pathway

Abstract: Osteoarthritis (OA) is a low-level inflammatory disease in which synovial macrophage M1 polarization exacerbates the progression of synovitis and OA. Notedly, the ROS (reactive oxygen species) level in macrophages is intimately implicated in macrophage M1 polarization. TRPV4 (transient receptor potential channel subfamily V member 4), as an ion channel, plays a pivotal role in oxidative stress and inflammation. In this study, we investigated the role of TRPV4 in OA progression and M1 macrophage polarization. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…Macrophage polarization is closely related to the inflammatory response when stimulated by inflammatory agents such as LPS, M0-type macrophages polarize into M1-type and secrete various pro-inflammatory mediators, thereby triggering an inflammatory cascade and promoting NLRP3 inflammasome activation. 33,34 The results revealed that PSPP-1 exerts antiinflammatory effects by regulating macrophage polarization, decreasing M1-type marker expressions (CD86 and iNOS) and increasing M2-type marker expressions (CD163 and ARG-1), thereby promoting the phenotypic switch from M1 to M2 and finally suppressing the inflammatory response. In addition, iNOS can catalyze arginine to produce high levels of NO and is involved in the inflammatory response, whereas ARG-1 is an active enzyme that can hydrolyze arginine, which inhibits the overproduction of NO and subsequently regulates the excess inflammatory response.…”
Section: ■ Discussionmentioning
confidence: 97%
“…Macrophage polarization is closely related to the inflammatory response when stimulated by inflammatory agents such as LPS, M0-type macrophages polarize into M1-type and secrete various pro-inflammatory mediators, thereby triggering an inflammatory cascade and promoting NLRP3 inflammasome activation. 33,34 The results revealed that PSPP-1 exerts antiinflammatory effects by regulating macrophage polarization, decreasing M1-type marker expressions (CD86 and iNOS) and increasing M2-type marker expressions (CD163 and ARG-1), thereby promoting the phenotypic switch from M1 to M2 and finally suppressing the inflammatory response. In addition, iNOS can catalyze arginine to produce high levels of NO and is involved in the inflammatory response, whereas ARG-1 is an active enzyme that can hydrolyze arginine, which inhibits the overproduction of NO and subsequently regulates the excess inflammatory response.…”
Section: ■ Discussionmentioning
confidence: 97%
“…Sun et al . (2022) revealed that inhibition of transient receptor potential channel subfamily V member 4 (TRVP4), an ion channel, inhibited M1 macrophage polarization through the ROS/NLRP3 pathway, consequently attenuating OA progression 146 . In the same manner, Luo et al .…”
Section: Signaling Pathways In Macrophage Polarizationmentioning
confidence: 93%
“…(2022) revealed that inhibition of transient receptor potential channel subfamily V member 4 (TRVP4), an ion channel, inhibited M1 macrophage polarization through the ROS/NLRP3 pathway, consequently attenuating OA progression. 146 In the same manner, Luo et al demonstrated that IL-37 induces M2 macrophage polarization through a process that requires IL-1R8/NLRP3, which appears to be a potential therapy target for temporomandibular joint OA. 147…”
Section: Nlrp3 Pathwaymentioning
confidence: 93%
“…Studies have shown that the infiltration of M1 synovial macrophages and the expression of TRPV4 were increased significantly in OA synovium, inhibition of TRPV4 delays OA progression by inhibiting M1 synovial macrophage polarization through the ROS/NLRP3 pathway (Ref. 100). Meanwhile specific TRPV4 knockout in chondrocytes can reduce OA severity caused by ageing in adult mice and intra-articular administration of a TRPV4 antagonist suppresses pain-related behaviours in a monoiodoacetic acid (MIA)-induced OA pain model (MIA rats), not due to inhibition of knee joint injury or inflammation caused by OA in MIA rats (Refs 101, 102, 103, 104).…”
Section: Trp and Autoimmune Diseasesmentioning
confidence: 99%